Imidacloprid soil drenches indirectly weaken the selection and predatory ability of the coccinellid predator Propylea japonica (Coleoptera: Coccinellidae) - Jie Zhang; Peng Huang; Yufang Pan; Yi Zhao; Jinai Yao; Deyi Yu (Scientific Reports)
Abstract Systemic insecticides are widely used to control sap-feeding pests, and their risks for natural enemies have become well-assessed in the past decades. However, most of these risk assessments focused on the direct effects when natural enemies come in contact with the sprayed leaves or forge contaminated prey. Consequently, the indirect impacts of systemic insecticides on regulating plant volatile organic compounds (VOCs) and how do these affect natural enemies have been overlooked. In the current study, we examined the indirect impact of imidacloprid soil drenches on prey selection behavior and functional response of the ladybird Propylea japonica. Our findings demonstrated that systemically applied insecticides could negatively affect natural enemy behaviors by disturbing VOCs emitted from plants. Compared with those exposed to fresh air and VOCs emitted from water-treated plants, P. japonica adults exposed to VOCs emitted from imidacloprid-treated plants were less chosen, and their attack rate (a) and handling times (h) markedly decreased, which potentially weaken biological control service. Meanwhile, we also found Frankliniella intonsa was less frequently chosen for imidacloprid-treated plants. Therefore, utilizing systemic imidacloprid to control pests needs to be cautiously considered when integrated pest management strategies are set up.